2014
DOI: 10.3390/ijerph110303271
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Silver Doped TiO2/Glass Fiber Photocatalyst under Visible Irradiation as an Indoor Air Germicide

Abstract: This study investigated the feasibility of using Ag-TiO2 photocatalyst supported on glass fiber (Ag-TiO2/GF) prepared by a sol-gel method as an indoor air germicide. An experimental model was designed to investigate the bacterial disinfection efficiency of Staphylococcus (Staph), the most popular bacterium in hospitals in Korea, by the Ag-TiO2/GF photocatalyst. The silver content in Ag/TiO2 was altered from 1 to 10% to investigate the optimal ratio of Ag doped on TiO2/glass fiber (TiO2/GF) for photocatalytic d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(21 citation statements)
references
References 54 publications
3
18
0
Order By: Relevance
“…The number of active sites could capture photo generated electron probably fell down with further increase in Ag percentage i.e. for 1.5 and 2% (w/w) Ag-doping [21]. EY sensitized Ag-doped TiO 2 (TiO 2 /Ag-1.0/EY) showed the highest absorbance with a maxima at 450 nm due to dye coloration.…”
Section: Resultsmentioning
confidence: 98%
“…The number of active sites could capture photo generated electron probably fell down with further increase in Ag percentage i.e. for 1.5 and 2% (w/w) Ag-doping [21]. EY sensitized Ag-doped TiO 2 (TiO 2 /Ag-1.0/EY) showed the highest absorbance with a maxima at 450 nm due to dye coloration.…”
Section: Resultsmentioning
confidence: 98%
“…Among these strategies, metals or non-metals as doping agents to enhance the photocatalytic activity of TiO 2 have been frequently used [17][18][19][20][21]. In our previous studies, we used Ag as a doping and sensitization to enhance the photocatalytic activity of TiO 2 deposited on glass fiber [22][23][24]. The synthesized photocatalysts exhibited high photocatalytic disinfection activity in removing Escherichia coli (E. coli) and Staphylococcus (Staph) in bioaerosols under visible light.…”
Section: Introductionmentioning
confidence: 99%
“…and O are three main elements in the sample. Pham and Lee16 indicated that the peaks (at 368.14 eV and 374.16 eV) represent the silver ions (Ag + ) and the two peaks (at 369.21 eV and 375.27 eV) represent the silver metal (Ag o ). The two big peaks located at 368.14 eV and 374.16 eV represent silver metal (Ag o ) and the two small peaks, located at 369.21 eV and 375.27 eV represent silver oxide (Ag2O)15 .…”
mentioning
confidence: 99%